USE OF NITRIC OXIDE THERAPY IN NEUROLOGICAL AND NOSOGENIC PSYCHOPATHOLOGICAL CONDITIONS DEVELOPING IN CANCER DISEASES OF THE REPRODUCTIVE SYSTEM - Yodgorov Jasurbek Jo’rayevich (World Scientific Research Journal, 2025)
Annotation This article analyzes neurological disorders and nosogenic psychopathological conditions (depression, anxiety states, cognitive decline) in patients with reproductive system cancers (endometrium, ovarian, prostate gland cancers, etc.). Studies devoted to the effectiveness of the use of nitric oxide (NO) as an endogenous vasodilator and neuromodulator in such cases are considered. The pathophysiological basis of nitric oxide therapy and scientific approaches to its clinical application are also analyzed.